Modes of relating to the new ICTs among older internet users: A qualitative approach - Coelho, A. R. (2022)
Older people have increasingly been using the new information and communication technologies (ICTs), namely the internet. Seeking to contribute with substantive information on their digital inclusion, this paper focuses on the adoption and use of ICTs by older adults, highlighting their experiences and considering their plurality. Taking a qualitative approach, the core goal of the empirical research underlying this paper was to understand what mechanisms and modalities configure the relationship of older internet users with the new ICTs. With that objective in mind, interviews were conducted with 20 internet users over the age of 60. Those interviews, which included a biographical element, were subjected to multi-categorical analysis. Results suggest a typology of modes of relating to the new ICTs among older internet users that reflects different trajectories, practices, skills, significances and impacts. The analysis shows how life trajectories and differentiated uses are reflected in equally differentiated impacts for older adults, contributing to their quality of life in different ways and to different degrees. Digital skills play a fundamental role in enhancing or limiting those effects. The results of this research help break down the stereotypes associated with the older generations and may have relevant implications for the design of digital inclusion policies and initiatives.